2021
DOI: 10.3390/land10111243
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Amazonia: The EU–Mercosur Trade Agreement and Deforestation

Abstract: The trade agreement between the European Union and the Mercosur countries will increase deforestation in the Mercosur countries and Brazil, in particular, if ratified by member countries. We use a computable general equilibrium model to analyze how trade, land use, and agricultural production will change as a result of the agreement. We then use a statistical model to spatially allocate the predicted deforestation within the Brazilian Amazon. The models estimate that the agreement will cause additional defores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
5
0
1
Order By: Relevance
“…The SDG indicator 15.3.1 revealed several land degradation hotspots in the Amazon basin between 2001 and 2020, most of which were located in the Brazilian states of Pará, Mato Grosso, Amazonas, and Rondônia. This result ties well with previous studies wherein such land degradation hotspots were identified (Anderson et al, 2018;Arima et al, 2021;Marengo et al, 2022).…”
Section: Long-term Land Degradation In the Amazon Basinsupporting
confidence: 92%
“…The SDG indicator 15.3.1 revealed several land degradation hotspots in the Amazon basin between 2001 and 2020, most of which were located in the Brazilian states of Pará, Mato Grosso, Amazonas, and Rondônia. This result ties well with previous studies wherein such land degradation hotspots were identified (Anderson et al, 2018;Arima et al, 2021;Marengo et al, 2022).…”
Section: Long-term Land Degradation In the Amazon Basinsupporting
confidence: 92%
“…Currently, additional pressures might be brought on Latin-American forests by the EU-Mercosur Trade Agreement (EMTA), which is being heavily discussed [28,[57][58][59][60][61]. The European Commission and the Mercosur region agreed on a trade-agreement (EMTA) in June 2019, that focuses on removing trade barriers between the two regions.…”
Section: Deforestation Pressures Coming From the Control Sectormentioning
confidence: 99%
“…They estimate the future deforestation to take place mostly in Pará (39.9%), Rondônia (32.6%) and Mato Grosso (25.2%) in the Amazon biome and Maranhão (31.6%), Piauí (21.3%), and Bahia (20.4%) in Cerrado. The authors also argue that the current Trade and Sustainable Development Chapter (TSDC) of the treaty remains inadequate to address the environmental challenges and deforestation drivers faced in these countries, thus it will create a large systemic drive for increased deforestation [28,60].…”
Section: Deforestation Pressures Coming From the Control Sectormentioning
confidence: 99%
“…Стороны достигли политического соглашения в июне 2019 г., в первый год президентства Болсонару, и даже за этот короткий период между инаугурацией и заключением политического соглашения ЕС -МЕРКОСУР темпы вырубки лесов Амазонки многократно возросли, причем треть из них приходилась на заповедные территории, а бразильские природоохранные организации выступили с открытым письмом к Европейской комиссии с требованием прекратить переговоры, гарантировать, что бразильские товары, поступающие на рынки ЕС, не ведут к увеличению вырубки лесов, и требовать у правительства Бразилии доказательств выполнения обязательств страны в рамках Парижского соглашения [FERN, 2019]. По мнению экологов, либерализация сельскохозяйственной продукции, прежде всего мясной, приведет к дальнейшим масштабным вырубкам в дельте Амазонки для создания пастбищных угодий [Arima et al, 2021]. Процесс подписания соглашения был заморожен по инициативе Австрии, Франции и Ирландии, которые заявили, что заблокируют ратификацию, если Болсонару не согласится на внедрение эффективных мер по борьбе с обезлесением и лесными пожарами [The Guardian, 2020].…”
Section: устойчивое управление лесамиunclassified